Diversidade críptica em Pipa carvalhoi? uma abordagem integrada - Lima, Luana Rodrigues (2019)
Anurans are one of the groups with the highest cryptic diversity. To uncover this diversity, the integrative taxonomy based on different sources of evidences has been employed. Pipa carvalhoi is an interesting species to be studied integrating diferent datasets. It has a disjoint distribution and low dispersal capacity suggesting that differentiation can be already occurred. In this study we use integrative taxonomy to assess Pipa carvalhoi diversity, asking whether independent lineages are in the process of differentiation, or have already become differentiated species. To test this hypothesis, morphological (tadpoles and adults), molecular (16S rRNA) and karyological data were analyzed. Three well-supported clades were recovered within Pipa carvalhoi. The structure of clades agree with drainage system: clade I occurs at the Northeastern Atlantic river basin, clade II at the San Francisco and East Atlantic river basins, and clade III at the Southeastern Atlantic river basin. The bPTP analysis recovered three candidate species, congruent with the clades recovered in the Bayesian Inference and Maximum Likelihood. Genetic distances among three clades of P. carvalhoi were higher that the expected value for interspecific divergence recovered using LocalMinima. Cytogenetic data did not differ among clades. The morphology of adults from different localities were similar, whereas the morphometric characters of tadpoles revealed morphological clusters with partial match with the genetic structure. Our results showed a strong genetic structure that indicates that P. carvalhoi is actually three cryptic species, apparently related to the hydrographic basins.